E-Learning Readiness Amongst Secondary School Teachers: A Case Study In Malacca, Malaysia - Goh, Pey Yun (2008)
The ineffectiveness of e-learning programs such as "School as Centre of ICT fo rthe Community" and the under-utilisation of e-lerning systems in schools in Malaysia bring out the issue of the readiness among teachers in embracing the e-learning program.